Marker-assisted introgression of a major broad spectrum blast resistance gene Pi54 into a popular rice variety Warangal Samba (WGL-14) - Ashwini, D; Venkanna, V; Chandra, B Satish; Devi, K Rukmini; Srividya, A; Lingaiah, N; Edukondalu, B; Madhu, Banoth; Kumar, R Shravan; Malathi , S; Hari, Y; Ramulu, Ch; et al. (Plant Science Today, 2024)
Warangal Samba (WGL-14) is a widely known medium slender-grain rice variety that matures within 135-140 days. This variety has been extensively cultivated in Telangana, India, due to its high yield potential of 7-7.5 t/ha and its favourable cooking qualities. However, it is highly susceptible to rice blast disease caused by the fungus Magnaporthe oryzae. This research sought to improve the blast resistance of WGL-14 by incorporating the Pi54 gene, a widely recognized blast resistance gene, using (MABB) along with selection based on phenotypic traits. NLR-145, a high-yielding rice variety containing the Pi54 gene, was used as the donor parent and crossed with WGL-14 to produce F1 plants. The Pi54MAS marker, which is specific to the Pi54 gene, was employed for foreground selection in F1, BC1F1, BC2F1 and BC3F1 generations, while background selection involved 80 parentals polymorphic SSR markers and phenotypic traits observed in each backcross generation. At BC3F5 generation, 28 lines were selected for their strong resistance to blast, high yields, plant type, grain characteristics and other traits comparable to the recurrent parent. These 28 lines were tested in yield trials during the wet seasons from 2018 to 2020 at the Regional Agricultural Research Station (RARS) in Warangal. At Advanced Varietal Trials (AVT), 3 lines namely WGL-1467, WGL-1472 and WGL-1473 were identified as having strong blast resistance and superior agronomic traits, closely resembling the original WGL-14.